1999
DOI: 10.1080/14622299050011281
|View full text |Cite
|
Sign up to set email alerts
|

Are higher doses of nicotine replacement more effective for smoking cessation?

Abstract: This study determined whether higher dose nicotine patches are more efficacious than lower dose patches among heavy smokers. A randomized double-blind study compared 0, 21, 35, and 42 mg/day of a 24-h patch in 1039 smokers (> or = 30 cigarettes/day) at 12 clinical sites in the USA and one in Australia. Daily patches were used for 6 weeks followed by tapering over the next 10 weeks. Weekly group therapy occurred. Biochemically validated self-reported quit rates at 6, 12, 26, and 52 weeks post-cessation were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(71 citation statements)
references
References 35 publications
5
66
0
Order By: Relevance
“…Further, as another indication that the 42 -mg dose of transdermal nicotine was well-tolerated, there was no difference in the rate of participant withdrawal from the study and no difference in the rate of participant adherence with patch use recommendations across the treatment arms. These results converge with the general literature on the use of higher doses of transdermal nicotine (see Dale et al, 1995 ;Fredrickson et al, 1995 ;Hatsukami et al, 2007 ;Hughes et al, 1999 ).…”
Section: Nicotine and Tobacco Researchsupporting
confidence: 89%
“…Further, as another indication that the 42 -mg dose of transdermal nicotine was well-tolerated, there was no difference in the rate of participant withdrawal from the study and no difference in the rate of participant adherence with patch use recommendations across the treatment arms. These results converge with the general literature on the use of higher doses of transdermal nicotine (see Dale et al, 1995 ;Fredrickson et al, 1995 ;Hatsukami et al, 2007 ;Hughes et al, 1999 ).…”
Section: Nicotine and Tobacco Researchsupporting
confidence: 89%
“…Although the point estimate favoured nicotine inhalers over placebo (odds ratio 2.17), these results were not conclusive because the 95% credible interval included unity (95% CrI 0. 59 15/44 9/43 Fiore et al 57 13/56 9/56 Glavas et al 58 10/57 4/55 Fiore et al 57 17/60 5/60 Paoletti et al 56 16/78 2/80 Westman et al 55 22/100 12/99 Abelin et al 53,54 21/103 15/104 Killen et al 52 15/109 11/108 Killen et al 52 28/113 10/107 Sachs et al 51 19/150 10/75 Kornitzer et al 50 33/120 17/120 Hurt et al 49 16/119 6/160 Hughes et al 46 16/154 3/144 Tonnesen et al 48 29/154 14/153 Richmond et al 47 4/160 6/160 Hughes et al 46 12/160 6/160 Hughes et al 46 27/184 16/185 Daughton et al 45 24/244 9/160 Jorenby et al 13 analysis, we found that all 7 pharmacotherapies were more efficacious than placebo ( Figure 6). …”
Section: Efficacy Of Smoking Cessation Pharmacotherapiesmentioning
confidence: 99%
“…The relapse rate in the first month of unaided abstinence is about 80 percent, and only 3-5 percent of untreated patients remain abstinent after 6 months (Polosa et al 2011;Gualano et al 2014). Furthermore, only about 20-25 percent of smokers will achieve abstinence with six months or more of goldstandard treatment (Hurt et al 1997;Hughes et al 1999;Jorenby et al 1999;Killen et al 1999;Holmes et al 2004Holmes et al , 2004. These observations suggest that smoking leads to persistent modifications in the brain that contribute to high relapse rates (DeBry & Tiffany 2008), an area of research which remains largely unexplored.…”
Section: Introductionmentioning
confidence: 90%